Implementation of daily patient‐reported outcome measurements to support children with cancer. Issue 11 (12th August 2021) - Meryk, Andreas; Kropshofer, Gabriele; Hetzer, Benjamin; Riedl, David; Lehmann, Jens; Rumpold, Gerhard; Haid, Alexandra; Holzner, Bernhard; Crazzolara, Roman
Abstract: Background: Several stakeholders, including patients and health care providers, suggest symptom self‐reporting measurements for a more patient‐directed cancer control approach. However, services tailored to measure daily reporting and implementing it in clinical care are lacking. This study aimed to evaluate the feasibility and value of daily patient‐reported outcome measures (PROMs) by children receiving chemotherapy for cancer. Methods: Health status was recorded daily with a web‐based child‐friendly patient portal (ePROtect). Following aspects of feasibility and usability were assessed: (a) the completion rate and time, (b) user feedback on usability and satisfaction, and (c) the performed interventions if moderate to severe symptom deterioration was noted. Results: Twelve children (median age: 7.2 years) were included. A total number of 891 daily reports were collected during the study period; the median percentage of ePROtect completion days was 85.3% (interquartile range [IQR] 64.2–100.0) and 55.9% (IQR 51.9–76.9) for inpatient and outpatient stay, respectively. Mean time to complete the questionnaire was 47.6 seconds. Severe symptoms were reported in 14.7% of measurement time points, which led to prompt health care interventions in 57 cases, including extension of supportive care ( n  = 37) and pre‐emptive inpatient admissions ( n  = 5). Over 80% of the patients (10/12) and their proxies (16/18) provided feedback with high rating for satisfaction (>90%) and usefulness (>80%) of ePROtect. Conclusion: Our study shows that daily symptom monitoring is feasible for all children with newly diagnosed cancer aged 5–18 years. Monitoring offers the opportunity to identify symptoms early and trigger appropriate clinical action.